Targeted and regulable expression of transgenes in hepatic stellate cells and myofibroblasts in culture and in vivo using an adenoviral Cre/loxP system to antagonise hepatic fibrosis. Issue 3 (6th September 2006) - Kinoshita, Kohji; Iimuro, Yuji; Fujimoto, Jiro; Inagaki, Yutaka; Namikawa, Kazuhiko; Kiyama, Hiroshi; Nakajima, Yuji; Otogawa, Kohji; Kawada, Norifumi; Friedman, Scott L; Ikeda, Kazuo
Abstract : Background: Activated hepatic stellate cells (HSCs) are an attractive target for antifibrotic therapy based on their key role in extracellular matrix accumulation during liver injury. Aim: : To develop a system for regulable and cell-specific gene expression in HSCs to enable targeted delivery of therapeutic genes. Method: Two types of recombinant adenoviral vectors were constructed, one expressing the Cre gene under the surveillance of specific promoters and the other containing a potent expression unit that was activated by Cre recombinase-mediated recombination to remove an upstream lox-flanked "stuffer" sequence, thereby amplifying the expression of downstream transgene of interest while maintaining specificity. Results: When the promoter of the collagen 1A2 gene drove Cre recombinase expression in primary quiescent rat HSC, modest green fluorescence protein (GFP) expression was observed. However, in activated HSC, the collagen promoter effectively drove Cre recombinase activity, as assessed by the increased expression of GFP. In contrast, GFP expression was barely observed when the collagen promoter was expressed in hepatocytes. HSC-specific expression of Smad7 considerably reduced the expression of type I collagen in culture and decreased fibrosis in two liver fibrosis models. Finally, to achieve targeted clearance of activated HSC in culture and in vivo, thymidine kinase was selectively expressed under the control of the collagen promoter, which conferred cell-specific killing by ganciclovir leading to reduced fibrosis. Conclusion: Our results show the potential utility of transcriptionally controlled gene therapy using a Cre/loxP system to ameliorate hepatic fibrosis in vivo.